Effect of a rigid structure on the dynamics of a bubble beneath the free surface. Issue 6 (November 2021) - Li, Shi-Min; Zhang, A-Man; Liu, Nian-Nian
Highlights: Establishes a numerical model used to model the bubble dynamics near a free surface and a rigid structure. More relevant researches on the bubble dynamics in the fields of underwater explosion and ocean engineering can be performed based on this work. Abstract: The coupling effect between a pulsating bubble and a free surface near a rigid structure is a complicated physical process. In this study, the evolution of an underwater explosion bubble and the free surface near a rigid structure is modeled by the boundary integral method. An approach of "double-node method" is used to maintain the stability of fluid-structure junction in the simulations, and meshes on the free surface and the structure are transformed to an open domain to ensure the calculation accuracy and efficiency. Validations are conducted against an underwater explosion experiment near a rigid structure. As a result, the simulations trace the jetting behavior of the bubble and the rise of the free surface. Finally, the bubble migration and the height of the free surface for different structure draughts are analyzed.